2015
DOI: 10.1007/s00294-015-0550-6
|View full text |Cite
|
Sign up to set email alerts
|

A self-encoded capsid derivative restricts Ty1 retrotransposition in Saccharomyces

Abstract: Retrotransposons and retroviral insertions have molded the genomes of many eukaryotes. Since retroelements transpose via an RNA intermediate, the additive nature of the replication cycle can result in massive increases in copy number if left unchecked. Host organisms have countered with several defense systems, including domestication of retroelement genes that now act as restriction factors to minimize propagation. We discovered a novel truncated form of the Saccharomyces Ty1 retrotransposon capsid protein, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 78 publications
(121 reference statements)
0
22
2
1
Order By: Relevance
“…Furthermore, it has been shown that proteolytic processing of the Gag protein of S . cerevisiae Ty1 transposable elements that assemble in the cytoplasm is also required for reverse transcription and transposition activity [67, 68]. Although we cannot rule out that in FVs Env binding to Gag might be a trigger to conformational rearrangement, we suggest that Gag cleavage to form p68, initiates the rearrangement of Gag, resulting in the appearance of the discrete capsid layer observed by cEM.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, it has been shown that proteolytic processing of the Gag protein of S . cerevisiae Ty1 transposable elements that assemble in the cytoplasm is also required for reverse transcription and transposition activity [67, 68]. Although we cannot rule out that in FVs Env binding to Gag might be a trigger to conformational rearrangement, we suggest that Gag cleavage to form p68, initiates the rearrangement of Gag, resulting in the appearance of the discrete capsid layer observed by cEM.…”
Section: Discussionmentioning
confidence: 96%
“…The relationship between altered Ty1 retromobility and altered Ty1i regulation reported here and the CNC phenomenon, in which increased Ty1 copy number leads to increased Ty1i expression[22,25], remains to be explored. It will be interesting to determine the molecular mechanism underlying CNC and the specific role that promoter competition and Mediator complex plays in this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Ty1 relies extensively on autoregulatory factors and host factors to successfully complete its mobility cycle and limit its mobility so as not to destabilize the host genome [18,22]. One mechanism of auto-inhibition known as copy number control (CNC) is defined by a copy number-dependent decrease in Ty1 retrotransposition observed both in S. cerevisiae and its close relative, S. paradoxus [23–25].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, none of those systems operate natively in S. cerevisiae or its sister species, S. paradoxus (Drinnenberg et al 2009). Instead, Ty1 mobility in S. cerevisiae and S. paradoxus is limited by a novel retroelement-directed restriction mechanism termed Copy Number Control (CNC) (Wilke et al 1992; Garfinkel et al 2003; Saha et al 2015; Garfinkel et al 2016; Ahn et al 2017). CNC is defined as a decrease in Ty1 mobility when additional copies of the Ty1 element are present in the genome.…”
Section: Introductionmentioning
confidence: 99%